Cost-effectiveness of MRI targeted biopsy strategies for diagnosing prostate cancer in Singapore - Cheng, Li-Jen (2022)
To evaluate the cost-effectiveness of six diagnostic strategies involving magnetic resonance imaging (MRI) targeted biopsy for diagnosing prostate cancer in initial and repeat biopsy settings from the Singapore healthcare system perspective.